The Principal’s Strategy in Shaping Students’ Religious Character at SMK Islam Al Muammilin Karangampel, Indramayu - Umar U (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to identify and analyze the principal's strategic design in shaping students' religious character, examine the implementation process, and evaluate the effectiveness of such strategies at SMK Islam Al Muammilin, Karangampel, Indramayu. The research is grounded in the critical role of school principals as educational leaders in creating an environment conducive to the formation of religious character, particularly in the modern era marked by moral and spiritual challenges. The decline of religious values among the younger generation has become a serious concern in Islamic education, requiring comprehensive and sustainable leadership strategies. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation from sources including the school principal, teachers, students, parents, school committee, and the head of the diniyah madrasa. Data analysis was conducted descriptively using triangulation techniques to ensure data validity. The findings reveal that: (1) The principal's strategic design includes integrating religious values into the formal curriculum, implementing routine religious programs such as congregational prayers and recitation of Juz Amma, and applying exemplary conduct (uswah hasanah) through the behavior of teachers and staff; (2) The implementation process involves mentoring teachers as religious role models, developing an Islam-based school culture, integrating mentoring programs and the Rohis organization, and actively engaging parents and the community; (3) The implemented strategies have proven effective in shaping students' religious character through an integrative, collaborative, and sustained approach encompassing cognitive, affective, and practical dimensions, supported by the principal's visionary leadership, teacher exemplariness, adequate facilities, and a strong synergy among school, family, and community.